Remembering home: Palestine from a distance - Noraini Md. Yusof; Ruzy Suliza Hashim; Raihanah, M.M (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
This paper examines the memories of a woman who was displaced and dispossessed of her home. Writing in retrospect of her childhood in Palestine, Ibtisam Barakat, in her memoir Tasting the Sky: A Palestinian Childhood, depicts with humor and resilience the love, attachment, struggle, and fear of the motherland she has left behind and of the new homeland she now inhabits. Between forgetting and remembering, Barakat's epistaloric narrative shows the conflict of a diasporic writer reconciling her past and her present. By investigating her notions of home, we draw conclusions on the memories and political concerns she evokes and how these recollections form her identity as a Muslim who is conscious of her roots.